Calcitonin Response to Naturally Occurring Ionized Hypercalcemia in Cats with Chronic Kidney Disease. (22nd February 2018) - van den Broek, D.H.N.; Geddes, R.F.; Williams, T.L.; Chang, Y.‐M.; Elliott, J.; Jepson, R.E.
Abstract : Background: Hypercalcemia is commonly associated with chronic kidney disease (CKD) in cats. Objectives: To explore the calcitonin response to naturally occurring ionized hypercalcemia in cats with azotemic CKD, and to assess the relationship of plasma calcitonin with ionized calcium, alkaline phosphatase (ALP), and urinary calcium excretion. Animals: Thirty‐three client‐owned cats with azotemic CKD and ionized hypercalcemia from first opinion practice. Methods: Cohort study. Calcitonin was measured with an immunoradiometric assay in heparinized plasma. Simple correlations were assessed with Kendall's rank correlation, and the within‐subject correlations of calcitonin with ionized calcium and other clinicopathological variables were calculated with a bivariate linear mixed effects model. Results: Calcitonin concentrations above the lower limit of detection (>1.2 pg/mL; range, 1.7–87.2 pg/mL) were observed in 11 of 33 hypercalcemic cats (responders). Blood ionized calcium concentration did not differ significantly between responders (median, 1.59 [1.46, 1.66] mmol/L) and nonresponders (median, 1.48 [1.43, 1.65] mmol/L; P = 0.22). No evidence was found for calcitonin and ionized calcium to correlate between cats (τb = 0.14; P = 0.31; n = 33), but significant positive correlation was evident within individual responders over time (within‐subject correlation coefficient [ r within ], 0.83; 95% confidence interval [CI], 0.63–0.92). Calcitonin correlated negatively over time with plasma ALP ( r within, −0.55; 95% CI, −0.79 to −0.16). Conclusions and Clinical Importance: Calcitonin does not appear to have an important role in calcium metabolism in cats with CKD.